Estudo de viabilidade da espectrocospia de infravemelho próximo para pagamento de cana por teor de sacarose - Pereira, Beatriz Benassi (Universidade Federal de São Carlos, 2021)
This study was developed in a sugarcane industry, in a sugarcane payment laboratory by sucrose content, where the payment of sugarcane is determined through analytical parameters such as Brix degree, Pol reading, fiber content, among others. The determination of these parameters is made by instrumental measurements that require intense operator attention. Thus, the purpose of this study is to demonstrate an improvement in the process, with the replacement of the conventional method, which requires a lot of labor and consumable materials, through the use of a near infrared spectrophotometer (NIR, near, infrared) coupled with the automation method. These models would be used to more quickly and cost-effectively predict the values of previously reported analytical parameters. The observed results showed that the use of NIR equipment is certified as a robust method for analyzing sugarcane, increasing the sampling of the raw material, ensuring reliable analytical results for the payment of sugarcane and with better economic viability when compared to the conventional method.
Feasibility study of near-infrared spectroscopy for sugarcane payment by sucrose content
Keywords: Cana-de-açucar; Pagamento de cana; Sacarose; Sugarcane; Payment of cane; Sucrose; NIR; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE